Assessment of hepatitis C monitoring adherence after viral eradication in veterans with substance use to improve care and surveil reinfection - Miranda L. Stratton, PharmD; Elayne D. Ansara, PharmD, BCPS, BCPP; Amanda P. Ifeachor, PharmD, MPH, BCPS; Kelly K. Houck, PharmD, BCPS; Suthat Liangpunsakul, MD, MPH; Katie J. Binger, PharmD, BCPP (Mental Health Clinician, 2022)
Introduction: Hepatitis C virus (HCV) incidence rates are rising for patients with substance use and/or SUDs. Guidelines provide monitoring recommendations to ensure remission after successful treatment. The study's objective was to identify gaps in follow-up for patients with documented substance use and/or SUD through assessment of adherence to guideline-recommended HCV RNA lab 12 months post-treatment. Methods: Patients treated for HCV through the Veteran Health Indiana Hepatitis C Pharmacy Clinic were retrospectively evaluated. Subjects were categorized based on the provider assigned for follow-up care after 12-week sustained virologic response (SVR12) labs (primary care provider [PCP] or HCV provider). The primary outcome was HCV RNA obtained 11 to 13 months post-treatment. Secondary outcomes were HCV RNA detected post-treatment, substance use, engagement in substance use treatment, and engagement with social work. Results: Two hundred forty-one patients were included in the HCV provider cohort and 139 in the PCP cohort. Forty-one patients did not have a specified clinic for follow-up treatment, and 20 patients did not achieve SVR12. Sixty-one patients (28%) in the HCV provider cohort completed a 12-month HCV RNA within 11 to 13 months post-treatment vs 15 patients (11%) in the PCP cohort (P ≤ .01). One patient had HCV RNA detected post-treatment. Discussion: This study reveals inadequate HCV post-treatment follow-up for patients with substance use and/or SUD. SUD is a chronic disease that requires continued monitoring to prevent complications. Further studies are needed to identify reinfection rates and improvements of care in this population.